2015
DOI: 10.1097/aud.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Insertion Angles, Default Frequency Allocations, and Spiral Ganglion Place Pitch in Cochlear Implants

Abstract: Objectives Commercially available cochlear implant systems attempt to deliver frequency information going down to a few hundred Hz, but the electrode arrays are not designed to reach the most apical regions of the cochlea which correspond to these low frequencies. This may cause a mismatch between the frequencies presented by a cochlear implant electrode array and the frequencies represented at the corresponding location in a normal hearing cochlea. In the following study, the mismatch between the frequency pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
180
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(204 citation statements)
references
References 43 publications
20
180
4
Order By: Relevance
“…The large variation in insertion depth was also reported by Landsberger et al [2015]. In contrast, they found a median insertion angle of the most apical electrode con-Audiol Neurotol 2019;24:38-48 DOI: 10.1159/000499154 tact of the Contour Advance electrode array of 375°, which is deeper than the median insertion angle of 307.3° in our study.…”
Section: Intracochlear Electrode Array Positioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The large variation in insertion depth was also reported by Landsberger et al [2015]. In contrast, they found a median insertion angle of the most apical electrode con-Audiol Neurotol 2019;24:38-48 DOI: 10.1159/000499154 tact of the Contour Advance electrode array of 375°, which is deeper than the median insertion angle of 307.3° in our study.…”
Section: Intracochlear Electrode Array Positioncontrasting
confidence: 55%
“…As the electrical stimulus activates spiral ganglion cells and not the organ of Corti, the classical place-pitch relation [Greenwood, 1990] has been amended for CI stimulation [Dorman et al, 2007;Stakhovskaya et al, 2007;Landsberger et al, 2015]. In pitch matching experiments in SSD patients implanted with a CI, the perceived pitch is 1 to 2 octaves lower than the pitch predicted by the amended place-pitch relation [Boëx et al, 2006;Dorman et al, 2007;Baumann and Nobbe, 2006;Schatzer et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CI subjects, although the cochlear place of stimulation for "apical" electrode pairs (given in Table 1) is unknown, a typical cochlear array insertion depth of 20 mm would place the apical-most electrode at a roughly ϳ1,000-Hz cochlear location (Stakhovskaya et al 2007; see also Landsberger et al 2015). Basal electrodes stimulate significantly higher-frequency locations.…”
Section: Interim Discussionmentioning
confidence: 99%
“…It was shown in earlier studies that deeply inserted electrode arrays result in increased intracochlear trauma and the loss of residual hearing , limited stimulation of the basal frequencies [Finley and Skinner, 2008] and confusion of the apical pitch due to neural interaction of the more densely located neural fibers in the apical regions in the cochlea [Gani et al, 2007]. On the other hand, other studies show that stimulation of the lower frequencies in the apical region of the cochlea are related to better speech perception outcomes [Hochmair et al, 2003;Yukawa et al, 2004], increased range of place pitches by stimulating a larger number of neural fibers [Landsberger et al, 2014], or reduced mismatch between the predicted and default frequencies by a further approximation of the normal frequency to place function of the cochlea [Landsberger et al, 2015]. Another study also showed that deeper inserted electrode arrays are not associated with scalar translocations [Wanna et al, 2014].…”
Section: Introductionmentioning
confidence: 98%